Self Help Group Analysis of Self Esteem and Stress Levels in Families with Patients with Depression - Errix Kristian Julianto (Journal for Quality in Public Health, 2019)
Increasing cases of depression and stress each year are related to increasing rates of divorce, academic or employment demands and social pressure. Not infrequently families who have family members who experience depression make it a family burden. Family perception of the stressor will affect the level of burden in the family and can affect the level of stress and family self esteem. The purpose of this study was to analyze the effect of Self Help Group on self esteem and Stress levels on Families with Depression at the Poly Psychology of the Kalitidu Health Center. The design of this study was True experimental with pre-posttest design. The sampling technique uses simple random sampling as many as 32 respondents, with 16 control group respondents and 16 family respondents with depressed patients who received a Self Help group. Data analysis techniques using Wilcoxon statistical test and mannwhitny. The results of this study indicate that there is an effect of self help group on self esteem and stress levels in families with depressed patients in mental health clinics of KalitiduBojonegoro with p value in the man whitney test of 0.005 in self esteem and 0.000 in stress levels and p value the value of the Wilcoxon test is 0.025 in self esteem and 0.001 in the stress level, all of which are less than the error level (α = 0.05). The effect of self help group on self esteem and stress level proves the change from before being treated in the intervention group, this proves that the treatment will be a stimulus in assessing a person's self-esteem and stress level with family members with depression